Role of interventional endoscopic ultrasound in a developing country - Hasan Maulahela; Nagita Gianty Annisa; Achmad Fauzi; Kaka Renaldi; Murdani Abdullah; Marcellus Simadibrata; Dadang Makmun; Ari Fahrial Syam (Korean Society of Gastrointestinal Endoscopy, 2023)
Background/Aims Endoscopic ultrasound (EUS) has become an essential diagnostic and therapeutic tool. EUS was introduced in 2013 in Indonesia and is considered relatively new. This study aimed to describe the current role of interventional EUS at our hospital as a part of the Indonesian tertiary health center experience. Methods This retrospective study included all patients who underwent interventional EUS (n=94) at our center between January 2015 and December 2020. Patient characteristics, technical success, clinical success, and adverse events associated with each type of interventional EUS procedure were evaluated. Results Altogether, 94 interventional EUS procedures were performed at our center between 2015 and 2020 including 75 cases of EUS-guided biliary drainage (EUS-BD), 14 cases of EUS-guided pancreatic fluid drainage, and 5 cases of EUS-guided celiac plexus neurolysis. The technical and clinical success rates of EUS-BD were 98.6% and 52%, respectively. The technical success rate was 100% for both EUS-guided pancreatic fluid drainage and EUS-guided celiac plexus neurolysis. The adverse event rates were 10.6% and 7.1% for EUS-BD and EUS-guided pancreatic fluid drainage, respectively. Conclusions EUS is an effective and safe tool for the treatment of gastrointestinal and biliary diseases. It has a low rate of adverse events, even in developing countries.